Targeted therapy or immunotherapy in BRAF-mutated metastatic melanoma: a Spanish center’s decade of experience - Sun, Chen; España, Sofia; Richarz, Nina; Solé-Blanch, Carme; Boada, Aram; Martinez-Cardús, Anna; Chu, Alan; Liu, Zongwen; Manzano, Jose Luis (Frontiers in Oncology, 2024)
Background： Targeted therapies and immunotherapy are currently considered the mainstay first-line treatment for advanced BRAF-mutated melanoma. However, the impact of treatment (targeted therapy and immunotherapy) and the prognostic factors are still not clear. Material and Methods: Medical records of 140 patients diagnosed with advanced melanoma between 2011 and 2021 were retrospectively reviewed to extract demographic, BRAF status, treatment, performance status, and survival data. ORR, PFS, and OS were compared between patients diagnosed with advanced melanoma and treated with first-line IT or BRAF/MEKi. The prognostic factors were assessed using Cox regression models. Results: In all patients and those treated with immunotherapy, we did not find any effect of BRAF status on ORR, PFS, or OS. In patients with BRAF-mutated melanoma, ORR was 43.8% vs. 70% (P=0.04), PFS was 19.2 vs. 11.5 months (p=0.22), and OS was 33.4 vs. 16.4 months for the immunotherapy and targeted therapy groups, respectively (P=0.04). ECOG, presence of brain metastases, and high LDH level from initiation of first-line treatment were all associated with differences in PFS and OS. Conclusion： Patients with advanced BRAF-mutated melanoma treated with first-line immunotherapy had a significantly longer PFS and OS than those treated with first-line BRAF/MEKi; however, first-line BRAF/MEKi treatment had a significantly higher ORR than first-line immunotherapy.